2020
DOI: 10.1186/s12882-020-01716-w
|View full text |Cite
|
Sign up to set email alerts
|

Oral Sucrosomial® iron versus intravenous iron for recovering iron deficiency anaemia in ND-CKD patients: a cost- minimization analysis

Abstract: Background: Oral iron is recommended as first line treatment of anemia in non-dialysis chronic kidney disease (ND-CKD) patients. Sucrosomial® iron, a new generation oral iron with high absorption and bioavailability and a low incidence of side effects, has shown to be not inferior to intravenous (IV) iron in the replacement of iron deficiency anemia in patients with ND-CKD. Besides the clinical benefit, it is also important to determine the comparative total costs of oral versus IV iron administrations. The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 19 publications
0
22
1
Order By: Relevance
“…It is a preparation of ferric pyrophosphate transported within a phospholipid and sucrose esters of fatty acid membrane. Due to its lack of direct contact with the intestinal mucosa, there has been a low report of side effects [ 39 ]. It also requires a lower drug dose than the ferrous variants [ 40 ].…”
Section: Managementmentioning
confidence: 99%
“…It is a preparation of ferric pyrophosphate transported within a phospholipid and sucrose esters of fatty acid membrane. Due to its lack of direct contact with the intestinal mucosa, there has been a low report of side effects [ 39 ]. It also requires a lower drug dose than the ferrous variants [ 40 ].…”
Section: Managementmentioning
confidence: 99%
“…As a result, compared to conventional oral iron salts, SI provides enhanced bioavailability with excellent gastrointestinal tolerability 5 . Oral SI has been shown to be effective and well tolerated in patients with ID associated with several conditions such as chronic renal disease, cancer, gastrointestinal disease, pulmonary arterial hypertension, gestation, orthopaedic or bariatric surgery, or in support of erythropoietin‐stimulating agent therapy 5,7,8,13–15 . We similarly observed a significant change in serum iron, serum ferritin and haemoglobin levels in favour of SI, despite the fact that the daily elemental iron dose was low (28 mg), being that of dietary supplementation rather than therapy, owing to the excellent bioavailability of the molecule.…”
Section: Discussionmentioning
confidence: 69%
“…All patients were on optimal guideline‐directed HF therapy that had been stable for at least 4 weeks prior to enrolment. Twenty‐five patients consecutive patients fulfilling the above criteria were treated with oral SI (one capsule daily containing 28 mg of SI and 70 mg of ascorbic acid, Sideral Forte®, WinMedica, Athens, Greece) for 3 months, based on the design of previous studies 7,8 . Another group of 25 patients, also fulfilling the above criteria, matched for age, gender and HF severity [New York Heart Association (NYHA) class and LVEF], not treated with iron supplementation, served as controls.…”
Section: Methodsmentioning
confidence: 99%
“…Campanella and coauthors had similar observations for IDA patients, as SRM was shown to be effective and well-tolerated in situations where parenteral therapy was indicated [45]. Some authors indicate the economic benefits of sucrosomial iron, especially when compared to parenteral therapy [42,46]. However, most studies have been carried out in small groups of patients [50].…”
Section: Sucrosomial Ironmentioning
confidence: 90%